Balanceamento de linha de montagem com o uso de heurística e simulação: estudo de caso na linha branca - Farnes, Vanessa Carolina Fernandes; Pereira, Néocles Alves (Revista Gestão da Produção Operações e Sistemas, 2007)
A proper dimensioning of the production capacity is essential for the positioning of an enterprise in a globalizedmarket. In enterprises with assembly line production, the dimensioning for the capacity is obtained by means ofthe balancing of the operations, by task assignment to the work stations, so that a performance measurement,such as the time, can be optimized. The line balancing methods considered in this paper correspond to a solutiondeveloped in an enterprise, a solution simply named as Balancer, and a heuristic tool named “PositionalWeight”. In addition, a probabilistic simulation tool was used in order to verify and analyze the heuristicsolution.Keywords: Line balancing, Capacity dimensioning, Positional weight, Simulation.